74 RNA-sequencing to dissect the role of selective HDAC6 inhibition on B cell signaling and germinal formation in lupus nephritis. (April 2019) - Reilly, Christopher M; Ren, Jingjing; Grammer, Amrie; Lipsky, Peter
Abstract : Background: Autoantibody production by plasma cells (PC) play a pivotal role in pathogenesis in of lupus nephritis (LN). The mechanism(s) of how B cells become pathogenic PC secreting autoantibody in SLE is incompletely characterized. In the current study, sought to determine if selective histone deacetylase (HDAC)6 inhibition would abrogate abnormal B cell activation in SLE. Methods: We treated 20-week-old NZB/W lupus mice with the selective HDAC6 inhibitor ACY-738 for four weeks beginning at 20 weeks-of age; at early disease. After 4 weeks-of-treatment, we used RNA-seq to determine the genetic signatures of splenocytes with and without treatment and applied signaling pathway computational analysis to reveal multiple pathways associated with B cell activation and differentiation in SLE that were modulated by HDAC6 inhibition. Results: Plasma cell development was abrogated as well as GC were greatly reduced. Additionally, kidney pathology was greatly reduced. When gene signature was compared to human lupus patients, the HDAC6 inhibitor treated mice showed several inflammatory pathways were decreased. Conclusions: Taken together, these studies suggest that HDAC6 inhibition decreased B cell activation signaling pathways and reduced PC differentiation in LN, suggesting that HDAC6 inhibition may represent an effective target to treat SLE. Funding Source(s): None